Standardization of Sterilization Protocol For Nodal Explants Of Field Grown Mature Tree Santalum Album L. - Radhika Thakkar; Dr.Sucheta Karande (International Journal of Pharma and Bio Sciences, 2022)
Santalum album L. is an important tree species cultivated in a wide range of areas because of its many applications. Indian sandalwood is a evergreen medium-sized tree. It is commercially important sp. For its heart wood essential oil, extensively used in medicines, cosmetics, perfume & incense industry. The technology has been used for quite some time in sandal for the regeneration of plants1-5 In vitro and particularly somatic embryogenesis. To establish aseptic culture standardization of sterilization techniques is most important. Studies on Santalum album L. were carried out in the tissue culture laboratory at Metrogen Tissue Culture Labrotary , Kalol,gandhinagar , Gujarat, India to standardize the in vitro propagation techniques. The present study was to investigate disinfection of explants taken from mature tare of Santalum album L. Explants were pre-sterilized with an aqueous solution of 0.1% Bavistin, 0.1% Tween 20 & etc; sterilization agents like HgCl2, with combinations at different time interval were used in present study. The preeminent result for nodal explant was obtained in 0.1% HgCl2 & etc; 0 1% Bavistin for 5 min was found to be the best. Effectively controlled the contaminant respectively in nodal & amp; internodal segments. Among the explants tested for multiple shoot induction, proved good result. The best Combination media for obtaining multiple shoot induction was MS+5.0 mgl-1 kin+ 2.0mgl-1 BAP for shoot tip explants.